Strengthening the Understanding of Aisyiyah Residents of North Tamantirto Branch regarding Cash Waqf Law - Asyiqin, Istianah Zainal; Yunita, Ani; Marwa, Muhammad Habibi Miftakhul (Berdikari: Jurnal Inovasi dan Penerapan Ipteks, 2024)
Law Number 41 of 2004 on Waqf defines waqf as an act in which the wakif separates or transfers part of his assets for the purposes of worship and/or public welfare in accordance with Sharia principles. Cash waqf, as a form of waqf, allows the wakif to entrust a certain amount of funds to the nadzir, who is tasked with managing them productively for the benefit of the mauquf alaih. Aisyiyah, a leading organisation in the religious, educational, social, and health fields, has become one of the main recipients of cash waqf in Indonesia. This organisation, in collaboration with Universitas Muhammadiyah Yogyakarta, initiated a program to increase public understanding of the law and concept of cash waqf. This program consists of lectures, studies, and discussions involving up to 50 participants, with the ultimate goal of spreading awareness through scientific publications, mass media, and educational videos. Post-program evaluation showed a significant increase in participants' understanding of legal aspects, basic concepts, and cash waqf management mechanisms in accordance with the fatwa of the Indonesian Ulema Council (MUI). These findings confirm the effectiveness of the program in increasing cash waqf literacy, as well as having the potential to encourage more optimal waqf management in society.